2018
DOI: 10.18295/squmj.2017.17.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Family Planning Counselling in North Jordan

Abstract: abstract:Objectives: Counselling plays a key role in enhancing reproductive services, providing contraceptionrelated information and supporting long-term family planning for women of childbearing age. This study aimed to evaluate family planning counselling sessions in selected governmental and private clinics in northern Jordan. Methods: This cross-sectional study was conducted between January and June 2016 in Irbid, Jordan. A total of 200 women attending two private clinics affiliated with the Jordanian Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
1
13
2
1
Order By: Relevance
“…A few studies have assessed the quality of family planning services offered to young people in Jordan. An evaluation of family planning counselling at selected public and private clinics noted that many government-run facilities lacked private rooms to offer confidential services (49). Other studies found widespread misconceptions among health professionals about the side-effects of family planning methods used by young people (50).…”
Section: Health Service Delivery Environmentmentioning
confidence: 99%
“…A few studies have assessed the quality of family planning services offered to young people in Jordan. An evaluation of family planning counselling at selected public and private clinics noted that many government-run facilities lacked private rooms to offer confidential services (49). Other studies found widespread misconceptions among health professionals about the side-effects of family planning methods used by young people (50).…”
Section: Health Service Delivery Environmentmentioning
confidence: 99%
“…Additionally, youth cite concerns that providers do not take them seriously, treat them like children, do not know what information youth need and view youth’s questions as inappropriate 21. An evaluation of services offered at selected public and private clinics in Jordan noted a lack of private rooms at Ministry of Health (MOH) clinics,22 which is a concern that has been echoed by youth 3. Another study found that providers often give incorrect information to youth regarding reproductive health, such as instructing them not to use contraception because of fears over the relationship between FP use and infertility 23.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 42.9% of the counselling sessions were deemed adequate, with providers applying 80% or more of the GATHER framework, while 26.8% of the sessions were deemed semi-adequate and 30.3% were considered inadequate. Counselling services provided in the governmental clinics were significantly less adequate than those provided in JAFPP clinics (Okour et al, 2018).…”
Section: Resultsmentioning
confidence: 77%